Bibliometric Analysis of Online Customer Loyalty - Loso Judijanto (West Science Interdisciplinary Studies, 2026)
This study aims to examine the intellectual structure, thematic evolution, and emerging trends in online customer loyalty research through a bibliometric approach. Data were collected from the Scopus database using relevant keywords related to online customer loyalty, covering publications over a defined period. The analysis was conducted using VOSviewer to perform performance analysis and science mapping, including co-occurrence and density visualizations. The findings reveal that customer satisfaction, customer loyalty, and sales constitute the core of the research domain, indicating a strong emphasis on the relationship between satisfaction and transactional outcomes. In addition, variables such as trust, service quality, and perceived value emerge as key relational drivers that strengthen loyalty formation in digital environments. The temporal analysis shows a shift toward technology-oriented themes, including\g machine learning, data mining, and sentiment analysis, reflecting the growing role of digital analytics in understanding customer behavior. This study contributes by providing a comprehensive mapping of the field and highlighting the transition from traditional relationship marketing perspectives to more integrated and data-driven approaches. The results offer valuable insights for both academics and practitioners in developing strategies to enhance customer loyalty in increasingly competitive online markets.